A framework for exploring digital entrepreneurship development from a social interaction perspective. (January 2023) - Zhao, Fang; Barratt-Pugh, Llandis; Suseno, Yuliani; Standen, Peter; Redmond, Janice
There is almost universal agreement within extant studies that digital technologies such as social media and digital platforms have accelerated and expanded social networks on an unprecedented scale, generating a transformative impact entrepreneurial processes and outcomes. However, there have been limited studies conducted to investigate this significant phenomenon. We aim to address this gap by providing a framework to extend research knowledge in this area. We specifically focus on the online and offline social contexts that are impacting on digital entrepreneurship (DE) development. We investigate the role of these often blended network relations in DE, placing human relations and social interaction at the centre of the study, and shifting away from previous purely technological approaches. While many existing studies in related fields focus on either social networks or social capital, we study the association between them, in the context of DE. As a contribution to extending existing theory, we propose a new research framework to underpin future study, based on established concepts within the literature and our own research evidence. This framework provides a model of the relational linkages between types of social networks and social capital to enable researchers to explore how they impact on the actions and outcomes of DE. Our purpose is to encourage, inform and guide future empirical research, to focus on and develop an understanding of the crucial role of social network interaction in DE development.